Health impacts from traffic related air pollution in Danish urban areas - Fenger, Jes; Jensen, Steen Solvang; Larsen, Poul Bo (Proceedings from the Annual Transport Conference at Aalborg University, 1995)
In most of the European cities air pollution has changed in recent years; previously the most serious problem was sulphur dioxide and soot from minor domestic heating plants; this has largely been solved by introduction of cleaner fuels and change in infrastructure. Now the increasing traffic emissions, notably of nitrogen oxides and volatile organic compounds, with the ensuing photochemical air pollution, attract most attention. Denmark has, for a series of geographical and meteorological reasons, relatively clean air. In urban areas, however, where the emission density is high and the dispersion of pollution is limited, impacts on human health and well-being must be considered. In the planning of a rational abatement strategy, including emission and air quality standards, it is not sufficient to determine pollution levels, it is also important to investigate to what extent people are actually exposed to them. Further, it is necessary to establish the relative contributions from various human activities.